Protest public relations communicating dissent and activism - Adi, Ana (Routledge new directions in public relations and communication research, 2019)
"Global movements and protests from the Arab Spring to the Occupy Movement have been attributed to growing access to social media, while without it, local causes like #bringbackourgirls and the ice bucket challenge may have otherwise remained unheard and unseen. Regardless of their nature - advocacy, activism, protest or dissent - and beyond the technological ability of digital and social media to connect support, these major events have all been the results of excellent communication and public relations. But PR remains seen only as the defender of corporate and capitalist interests, and therefore resistant to outside voices such as activists, NGOs, union members, protesters and whistle-blowers. Drawing on contributions from around the world to examine the concepts and practice of 'activist', 'protest' and 'dissent' public relations, this book challenges this view. Using a range of international examples, it explores the changing nature of protest and its relationship with PR and provides a radical analysis of the communication strategies and tactics of social movements and activist groups and their campaigns. This thought-provoking collection will be of interest to researchers and advanced students of public relations, strategic communication, political science, politics, journalism, marketing, and advertising, and also to PR professionals in think tanks and NGOs"--